Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/01913120600820112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes of Mitochondria in the Cultivated Skin Fibroblasts of Patients with Point Mutations in Mitochondrial DNA

Abstract: Mitochondrial disorders represent a heterogeneous group of multisystem diseases with extreme variability in clinical phenotype. The diagnosis of mitochondrial disorders relies heavily on extensive biochemical and molecular analyses combined with morphological studies including electron microscopy. Although muscle is the tissue of choice for electron microscopic studies, the authors investigated cultivated human skin fibroblasts (HSF) harboring 3 different pathologic mtDNA mutations: 3243A > G, 8344A > G, 8993T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…9). In contrast to mitochondria of father’s cells, which are filamentous as commonly seen in cultured fibroblasts, 20 mitochondria of R cells appear to be shorter and distorted. Another noticeable feature of R cells was the presence of large vesicles not seen in F cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 68%
“…9). In contrast to mitochondria of father’s cells, which are filamentous as commonly seen in cultured fibroblasts, 20 mitochondria of R cells appear to be shorter and distorted. Another noticeable feature of R cells was the presence of large vesicles not seen in F cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 68%
“…The proportions of wild-type to mutant mtDNA were measured using a PhosphorImager and ImageQuant software (Molecular Dynamics). The levels of heteroplasmy of the 3243A>G and 8344A>G mutations were determined as described elsewhere [16].…”
Section: Mtdna Analysismentioning
confidence: 99%
“…Bernier et al [25] demonstrated ultrastructural cardiac abnormalities in only 3% of their patients studied. Fibroblasts can sometimes demonstrate ultrastructural mitochondrial abnormalities, especially in patients with mitochondrial DNA defects [46]. Patients with significant central nervous system involvement may receive a brain biopsy, but brain pathology is also nonspecific, demonstrating focal necrosis, a loss of cortical neurons, reactive astrogliosis, astrocytic inclusions, demyelination, spongiosis, endothelial proliferation, or capillary hyperplasia [17].…”
Section: Pathology Of Other Tissuesmentioning
confidence: 99%